Edukreasi Lingkungan: Pembuatan Kerjainan Tangan Dari Sampah Tutup Botol Untuk Pengenalan Satwa Dan Peningkatan Kesadaran Lingkungan - Setiawan, Heru; Lutfiani, Salsabila Arzaqia; Putri, Siska Aulia; Hasanah, Uswatun (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
This community service initiative at RA Muslimat NU Kalegen 2 addressed the escalating environmental issues linked to improper waste disposal. Focusing on transforming plastic bottle caps into educational toys, the project aimed to instill environmental consciousness and creativity in children. Through direct demonstrations and engagement, participants were encouraged to repurpose waste materials. The positive outcomes, including increased knowledge, skills, and creativity among the children, were evident. The high satisfaction levels from participants underscore the success of the program in promoting sustainability and environmental responsibility among young minds.